Exploration of blended learning reform in practical public health talent training - Xiangrong XU; Shengfeng WANG; Jianrong ZHANG; Yanping ZHU; Jing HE; Yajun XU (Zhongguo gonggong weisheng)
Under the implementation of the "Healthy China 2030" Planning Outline, the construction of public health practice bases and the cultivation of practice-oriented public health professionals have become increasingly important. School of Public Health, Peking University based on the integration of its existing practical teaching bases, has explored a new practical teaching model. This model uses traditional base practice as the main thread, enhanced by practical micro-courses, and verified by practical case assessments. The school has strengthened the construction of a "dual-qualified" faculty team in public health, established a comprehensive practical teaching evaluation system, and built a high-level practical teaching platform for public health. This new model provides a valuable reference for cultivating practice-oriented public health professionals who meet the needs of social development and public health undertakings.